A review of organophosphate esters in indoor dust, air, hand wipes and silicone wristbands: Implications for human exposure. (January 2021) - Hou, Minmin; Shi, Yali; Na, Guangshui; Cai, Yaqi
Graphical abstract: Highlights: OPE contamination in indoor air and dust in literature over past ten years are reviewed. Sampling strategies are related to OPE exposure assessment results. OPE particle size distributions and bioavailability in dust are affected by factors. Validity of hand wipe and wristband as exposure indicator are not clear for many OPEs. Human direct exposure to di-OPEs should be concerned. Abstract: The ubiquity of organophosphate esters (OPEs) in various environmental matrices inevitably pose human exposure risks. Numerous studies have investigated human exposure pathways to OPEs, including air inhalation, dust ingestion, dermal contact, and dietary and drinking water intake, and have indicated that indoor dust and indoor air routes are frequently the two main human exposure pathways. This article reviews the literature on OPE contamination in indoor air and dust from various microenvironments and on OPE particle size distributions and bioavailability in dust conducted over the past 10 years. Ways in which sampling strategies are related to the uncertainty of exposure assessment results and comparability among different studies in terms of sampling tools, sampling sites, and sample types are addressed. Also, the associations of OPEs in indoor dust/air with human biological samples were summarized. Studies on two emerging matrices, hand wipes and silicone wristbands, are demonstrated to be more comprehensive and accurate in reflecting personal human exposure to OPEs in microenvironments and are summarized. Given the direct application of some diester OPEs (di-OPEs) in numerous products, research on their existence in indoor dust and food and on their effects on human urine are also discussed. Finally, related research trends and avenues for future research are prospected.